2019
DOI: 10.1021/acs.iecr.9b01693
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Polymeric Solid Framework-Based Organic Phase-Change Materials for Thermal Energy Storage

Abstract: Phase-change materials (PCMs) are utilized for thermal energy storage (TES) to bridge the gap between supply and demand of energy. Organic PCMs, similar to paraffins, fatty acids, and polyethylene glycol, are extensively explored, thanks to their high TES capacity (∼5–10 times more than the sensible heat storage of water/rock), wide temperature range (spanning from −5 °C to 190 °C), good thermal stability over heating–cooling cycles (∼100 cycles), etc. However, “leakage” of PCMs upon transformation from solid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 227 publications
0
44
0
Order By: Relevance
“…It has been reported that water, molten salts, and concrete can be used as energy sources when the sensible heat storage technique is used to address the energy problems and mannitol and microcapsulated phase change materials (PCMs) can be used as energy sources when the latent heat storage technique is used to meet the energy demand. [1][2][3][4][5][6][7] The heat storage density and longterm heat storage capacity achieved using the CHS technique was better than the heat storage density and long-term heat storage capacity achieved using the other two techniques. [8][9][10][11][12][13] Therefore, in our previous studies, the CHS technique has received attention for energy conservation.…”
Section: Introductionmentioning
confidence: 84%
“…It has been reported that water, molten salts, and concrete can be used as energy sources when the sensible heat storage technique is used to address the energy problems and mannitol and microcapsulated phase change materials (PCMs) can be used as energy sources when the latent heat storage technique is used to meet the energy demand. [1][2][3][4][5][6][7] The heat storage density and longterm heat storage capacity achieved using the CHS technique was better than the heat storage density and long-term heat storage capacity achieved using the other two techniques. [8][9][10][11][12][13] Therefore, in our previous studies, the CHS technique has received attention for energy conservation.…”
Section: Introductionmentioning
confidence: 84%
“…The most important classification of polysaccharides is carboxymethyl cellulose. CMC is a semi-crystalline, water-soluble, non-toxic [53,54], low-cost [55][56][57], and biodegradable material [58][59][60] with excellent film-forming ability; however, it suffers from low conductivity [61,62] and the lack of strength [63]. Extensive studies have been conducted on the CMC application in single polymer electrolyte systems, however, some problems limit its application in this field due to small elongation at break, exceptionally stiff behavior, (less than 8%), and losing the electrochemical stability required for electrochemical devices.…”
Section: Carboxymethyl Cellulose (Cmc)mentioning
confidence: 99%
“…[ 3 ] Organic PCMs, such as polyethylene glycol, fatty alcohols, paraffin, and fatty acids, generally exhibit large latent heat and solid–liquid phase transitions, rendering them highly suitable for the preparation of thermal energy storage materials. [ 4,5 ] These phase changes are governed by diverse intermolecular interactions, such as van der Waals forces, dipole–dipole interactions, and hydrogen bonding. [ 6 ] Adjusting these interactions during phase transitions allows control not only over thermal energy but self‐assembled structures as well via molecular arrangement.…”
Section: Figurementioning
confidence: 99%